A fuzzy based hybrid decision-making framework to examine the safety risk factors of healthcare workers during COVID-19 outbreak. Issue 1 (3rd April 2022) - Rathore, Bhawana; Gupta, Rohit
ABSTRACT: The consciousness of safety risk factors and the emergence of WHO guidelines for the preparedness of health care workers have pushed the health care systems to take proactive decisions to maintain a safe and productive working environment during the COVID-19 outbreak. In order to provide this working environment, detailed identification, and analysis of safety risk factors are required. In this context, we proposed a hybrid fuzzy-based decision-making framework to rank the Indian hospitals based on the prevalence of safety risk factors among the health care workers. First, fifteen relevant safety risk factors are identified with the help of the Fuzzy Delphi Method (FDM). Second, the weights of categories and their respective factors are computed and are ranked based on their criticality by the Fuzzy Analytic Hierarchy Process (FAHP). Finally, Indian Hospitals are ranked based on these factors using the Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (FTOPSIS).